Exploring the Motivations, Expectations, and Experiences of Students Who Study in Global Settings - Salyers, Vince; Carston, Cathy S.; Dean, Yasmin; London, Chad (Journal of International Students, 2015)
An increasing trend of universities is to provide students with opportunities to engage in global learning experiences (GLE) as part of their program of study. While there are numerous papers on the benefits of international and study abroad programs, there is little research on factors that impact GLE. This study evaluated the student perspective through qualitative and quantitative responses to surveys and questions posed during a period of three years. The results suggested that students’ motivation and expectations of the experiences were varied. Moreover, planning is critical for GLE experiences to have a positive impact on students.